On the bimodality of the distribution of the S&P 500's distortion: Empirical evidence and theoretical explanations - Noemi Schmitt; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2017)
After showing that the distribution of the S&P 500's distortion, i.e. the log difference between its real stock market index and its real fundamental value, is bimodal, we demonstrate that agentbased financial market models may explain this puzzling observation. Within these models, speculators apply technical and fundamental analysis to predict asset prices. Since destabilizing technical trading dominates the market near the fundamental value, asset prices tend to be either overvalued or undervalued. Interestingly, the bimodality of the distribution of the S&P 500's distortion confirms an implicit prediction of a number of seminal agent-based financial market models.
Keywords: G12; G14; G17; 330; stock market dynamics; bubbles and crashes; chartists and fundamentalists; nonlinear dynamics; bimodality tests; time series analysis